My doubt is related to Cramer's rule with this exercise. I need to get the parametric equations of $$x-y-z-1=0,$$ $$y-t-z=0.$$

I assign parameters as $z := \lambda, t := \beta$, so I get

$$x-y=1+\lambda,$$ $$y=2+\beta$$

Now, using Cramer's rule is

$$x = \frac{\begin{vmatrix} 1+\lambda & -1 \\ 2+\beta & 1 \end{vmatrix}}{\begin{vmatrix} 1 & -1 \\ 0 & 1 \end{vmatrix}} = \frac{1+\lambda-2-\beta}{1}= \lambda-1-\beta$$

But if we solve in a traditional way, $$x=y+1+\lambda=3+\lambda+\beta.$$

In fact, the first solution for $x$ doesn't satisfy the system of equations. However, I think that the Cramer's rule is right.

So, what is wrong here?



It's because$$\begin{vmatrix}1+\lambda&-1\\2+\beta&1\end{vmatrix}=1+\lambda-(-1)\times(2+\beta)=3+\lambda+\beta.$$

  • $\begingroup$ All right... I was blind! Thanks! $\endgroup$ – user183002 Nov 3 '19 at 10:57

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.